Contribution of School Well-Being in Reducing Academic Procrastination Among Student at SMAN 1 Padang Sago - Roslinda (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
This research aims to investigate whether school well-being contributes to reducing academic procrastination among students of SMAN 1 Padang Sago. This research is designed as a quantitative study with a correlational research type. The subjects in this study were 172 students from grades XI and XII at SMAN 1 Padang Sago, with a sampling technique using proportionate stratified random sampling. Data collection techniques for the variable of school well-being were the school well-being scale developed by Rosma (2022) based on the dimensions of school well-being according to Konu & Rimpel (2002), while the variable of academic procrastination was the academic procrastination scale developed by Firdana (2022) based on the dimensions of academic procrastination proposed by Ferrari et al. (1995). The data analysis used in this study was simple linear regression analysis. The results showed that school well-being contributed to reducing academic procrastination among students of SMAN 1 Padang Sago by 14%. It can be concluded that the higher the school well-being, the lower the academic procrastination among students, and vice versa.